Duplex stainless steel fabricated by selective laser melting - Microstructural and mechanical properties - Hengsbach, Florian; Koppa, Peter; Duschik, Kristina; Holzweissig, Martin Joachim; Burns, Madison; Nellesen, Jens; Tillmann, Wolfgang; Tröster, Thomas; Hoyer, Kay-Peter; Schaper, Mirko (Materials & Design)

Recyclingkonzepte für hybride Strukturen - Schweizer, Swetlana; Tröster, Thomas (Carbon Composites Magazin)

Technikevaluation für die generative Fertigung eines Serien-Radträgers - Grienitz, Volker; Tröster, Thomas; Meiners, Stefan (ATZ - Automobiltechnische Zeitschrift)

Parameterstudien an intrinsisch hergestellten Metall-FVK-Hybridstrukturen mittels RTM-Verfahren - Wang, Z.; Tröster, Thomas

Experimentelle Untersuchung und Analyse des Energieabsorptionsverhaltens axial belasteter Faserverbundkunststoffe - Striewe, Jan André; Reuter, C.; Oberkönig, C.; Lauter, C.; Tröster, Thomas

Manufacturing and Crashworthiness of Fabric Reinforced Thermoplastic Composites - Striewe, Jan André; Lauter, C.; Reuter, C.; Tröster, Thomas

Innovative largescale Production Process for multilayered Sheet-Metal-FRP-Structures - Striewe, Jan André; Reuter, C.; Lauter, C.; Tröster, Thomas

CarS: Carbon Fiber Reinforced Steel for Structural Automotive Applications - Wang, Z.; Lauter, C.; Löseke, Julian; Tröster, Thomas

Neue Prototypen-Werkzeugtechnologie für Bipolarplatten und Batteriekomponenten - Hickmann, T.; Ahlers, Dominik; Tröster, Thomas (Der Stahlformenbauer)

Influences of interface and surface pretreatment on the mechanical properties of metal-CFRP hybrid structures manufactured by resin transfer moulding - Tröster, Thomas; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Bobbert, Mathias; Lauter, Christian; Zinn, Carolin; Wang, Zheng; Dammann, Christian (International Journal of Automotive Composites)

Laserbehandlung intrinsisch gefertigter Hybride - strukturelle, mechanische und korrosive Eigenschaften - Zinn, C.; Bobbert, Mathias; Dammann, C.; Wang, Z.; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Tröster, Thomas

Shear edge tests: a benchmark in investigating the influence of different surface pretreatment methods on the shear stress of intrinsically manufactured metal-CFRP hybrids - Weidenmann, Kay André; Pottmeyer, Florentin; Wang, Zheng; Tröster, Thomas; Meiners, Dieter; Zinn, Carolin; Schaper, Mirko; Gonzalez, Jonathan Serna (International Journal of Automotive Composites)

Influences of interface and surface pretreatment on the mechanical properties of metal-CFRP hybrid structures manufactured by resin transfer moulding - Tröster, Thomas; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Bobbert, Mathias; Lauter, Christian; Zinn, Carolin; Wang, Zheng; Dammann, Christian (International Journal of Automotive Composites)

Intrinsische Herstellung hybrider Strukturkomponenten in einen modifizierte RTM-Prozess - Bobbert, Mathias; Dammann, C.; Wang, Z.; Zinn, C.; Mahnken, Rolf; Schaper, Mirko; Tröster, Thomas

Novel Process Approach for in-situ Insertion of Functional Elements in RTM-Applications - Bobbert, Mathias; Augethaler, Florian; Wang, Zheng; Tröster, Thomas; Meschut, Gerson (Journal of Materials Science Research)
Lightweight design in vehicles leads to an increasing use of fibre-reinforced-plastics (FRP). To ensure the possibility of detachable joints in those constructions specific joining technologies have to be developed. Available technologies are not suitable for mass production or are leading to damage in the FRP. The aim of this paper is to show the possibilities and the general feasibility of a new process approach for the application of functional elements in FRP or hybrid materials during resin transfer moulding (RTM) processes. Therefore the movement of the RTM-tool-punch is utilised to produce an interlock between the splay stud and the fibres of the non-consolidated preform. This enables the application of the elements during the RTM-process. The resin infusion leads to the consolidation of the CFRP and a further fixation of the splay stud. Pull-out-tests as well as torsion tests are showing the mechanical performance of the joints.

Manufacturing and investigation of steel-CFRP hybrid pillar structures for automotive applications by intrinsic resin transfer moulding technology - Tröster, Thomas; Camberg, Alan Adam; Sanitther, Bamned; Wang, Zheng; Lauter, Christian (International Journal of Automotive Composites)

Large-Scale Production of High-Performance Fiber-Metal-Laminates by Prepreg-Press-Technology - Lauter, Christian; Reuter, Corin; Wu, Shuang; Tröster, Thomas (International Journal of Mechanical, Aerospace, Industrial, Mechatronic and Manufacturing Engineering)

Fatigue Strength Prediction for Titanium Alloy TiAl6V4 Manufactured by Selective Laser Melting - Leuders, Stefan; Vollmer, Malte; Brenne, Florian; Tröster, Thomas; Niendorf, Thomas (Metallurgical and Materials Transactions A)

Multi-axial Material Testing at High Strain Rates in High Speed Cupping Tests - Weiß Borkowski, Nathalie; Marten, Thorsten; Block, Holger; Tröster, Thomas

Bestimmung und Optimierung von Eigenspannungen in hybriden Werkstoffsystemen aus Metall und Faserverbundkunststoff (FVK) - Frantz, M.; Lauter, C.; Wang, Z.; Tröster, Thomas